2002
DOI: 10.1093/annonc/mdf013
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose oral methotrexate and cyclophosphamide in metastatic breast cancer: antitumor activity and correlation with vascular endothelial growth factor levels

Abstract: Continuously low-dose CTX and MTX is minimally toxic and effective in heavily pretreated breast cancer patients. A drop in VEGF was associated with the treatment and so alternative hypotheses, other than that of direct toxicity on tumor cells, must be favored when trying to explain the anticancer effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
274
2
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(302 citation statements)
references
References 34 publications
17
274
2
9
Order By: Relevance
“…In our study, the individual plasma VEGF concentrations of patients initially increased when compared to the baseline values in the first 3 weeks and then at lower doses constantly decreased. Despite the presence of a high variability, VEGF plasma levels may reflect both the initial elevated hypoxia of tumour tissue caused by the antiangiogenic therapy, as previously shown (Bocci et al, 2004;Motzer et al, 2006), and the low rate of VEGF secretion by tumour or tumourassociated stromal cells due to the long-term therapy (Colleoni et al, 2002). This PK/PD study underlines the importance to conduct further comparative studies with BSC or bevacizumab to establish the feasibility of metronomic irinotecan approach.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In our study, the individual plasma VEGF concentrations of patients initially increased when compared to the baseline values in the first 3 weeks and then at lower doses constantly decreased. Despite the presence of a high variability, VEGF plasma levels may reflect both the initial elevated hypoxia of tumour tissue caused by the antiangiogenic therapy, as previously shown (Bocci et al, 2004;Motzer et al, 2006), and the low rate of VEGF secretion by tumour or tumourassociated stromal cells due to the long-term therapy (Colleoni et al, 2002). This PK/PD study underlines the importance to conduct further comparative studies with BSC or bevacizumab to establish the feasibility of metronomic irinotecan approach.…”
Section: Discussionmentioning
confidence: 64%
“…However, the heterogeneous patient population, the drugs that were involved and the lack of a preclinical investigation of the doses that were used, and combination of drugs used all could have affected the outcome of the results. Colleoni et al (2002) described a reduction in serum VEGF of both responders and non-responders in breast cancer metastatic patients treated with metronomic CTX. In our study, the individual plasma VEGF concentrations of patients initially increased when compared to the baseline values in the first 3 weeks and then at lower doses constantly decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Such regimen involves the frequent administration of conventional chemotherapeutic agents (e.g., cyclophosphamide, vinblastine, topotecan, cisplatin) at very low doses to target activated endothelial cells in tumors, the advantages of which include minimal adverse effects and scarce chance of developing acquired drug resistance. Indeed, preclinical [2][3][4][5] and clinical studies [6][7][8] have demonstrated the antitumor efficacy and the superiority of metronomic chemotherapy compared with its maximum tolerated dose (MTD) counterpart. Endostatin, tumstatin, and thrombospondins are endogenous proteins or protein fragments with antiangiogenic property.…”
mentioning
confidence: 99%
“…56 CTX has also been used with low-dose methotrexate in the treatment of early breast cancer and the inhibition of angiogenesis is caused by a decrease in vascular endothelial growth factor. 57 …”
Section: Cyclophosphamidementioning
confidence: 99%